การวิเคราะห์ผลของการใช้เวลาในการปฏิบัติภาระงานสอนที่มีต่อประสิทธิภาพการสอนของครูในสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - ทับทิมทอง พรทิพย์; สุดรุ่ง จุไรรัตน์ (An Online Journal of Education, 2018)
This research is purposed to analyze the Effects of Task Operating Time on Teaching Efficiency of Teachers in The Office of The Basic Education Commission. The sample population is consisted of 385 teachers worked in small, medium, large, and extra large sized secondary schools. The instrument of the research is a questionnaire typed in check list, rating scale and open-ended. The result of this research reveals that the effect of task operating time on learning and teaching is positive to teaching and learning efficiency highly resulted in the students’ learning process while the negative result is the effect of task operating time on schools’ educational quality development favorably shown in the students’ success rate.